Path Analysis of Digital Economy Driving the Enhancement of Export Resilience in Foshan’s Manufacturing Enterprises - Huang, Jingqi; Li, Tong; Feng, Jiajun (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
With the rapid development of the digital economy, Foshan, a key manufacturing hub in China, faces immense pressure for transformation and upgrading. The rise of the digital economy has brought new opportunities and challenges to Foshan’s manufacturing export enterprises. This paper explores the path through which the digital economy enhances the export resilience of Foshan’s manufacturing enterprises through the integration of digital and physical industries. The study finds that the digital economy has a profound impact on the export resilience of Foshan’s manufacturing enterprises, enhancing their competitiveness in the global market. Through digital transformation, supply chain optimization, and innovation-driven growth, Foshan’s manufacturing sector can effectively strengthen its export resilience, overcoming uncertainties and risks in global trade. This paper proposes specific paths for enhancing export resilience in Foshan’s manufacturing enterprises driven by the digital economy and offers policy recommendations to promote high-quality development and international competitiveness in Foshan’s manufacturing sector.